Clinical and hormonal characteristics of women with various phenotypes of polycystic ovary syndrome (Annals of Medical Research, 2021)
Aim: The goal of this study is to identify clinical and hormonal characteristics of women with various phenotypes of polycystic ovary syndrome. Material and Methods: One hundred seventy eight cases, between the ages 18-30, diagnosed with PCOS, up to Rotterdam criteria, in our clinic between February 2015 -November 2018 were recruited in this cross sectional study. Results: The number was declined 89 by using National Institutes of Health criteria, 132 up to Androgen Excess and PCOS Society criteria. 34.83% of the patients were phenotype A, 15.16% were phenotype B, 24.15% were phenotype C and 25.84% were phenotype D. When we compared the different phenotypes with each other, body mass index, fasting glucose, postprandial glucose, fasting insulin and homeostatic model assessment for insulin resistance were found to be higher in phenotype A. In addition, luteinizing hormone and luteinizing hormone to follicle stimulating hormone ratio was higher in phenotype D than in B and C. When multivariate analysis was performed, body mass index was found to be as a single statistically significant predictive factor on IR. Conclusion: Body mass index was the most effective factor on insulin resistance and the mean body mass index was significantly higher in phenotype A.
Keywords: Hirsutism; hyperandrogenism; insulin resistance; phenotype; polycystic ovary syndrome